Pengaruh Senam Lansia terhadap Penurunan Skala Insomnia Ada Lansia di Panti Wredha Dewanata Cilacap - Sumedi, Taat; Wahyudi,; Kuswati, Ani (Jurusan Keperawatan FIKES UNSOED, 2010)
Insomnia is one of sleep disturbance that is usually happened to elderly. Insomnia relates closely with sleep quality decreasing so that it makes sleep does not have quality. Physical exercise is authentically repair sleep quality of elderly. One of physical exercise kind that can be done by elderly is elderly fit gymnastics. The objective of this research was to know the influence of elderly fit gymnastics towards insomnia scale decreasing at Dewanata Elderly Orphanage of Cilacap. Quasi experiment of research sort with pretest-posttest without control group approach. The population of this research was all elderly clients at Dewanata Elderly Orphanage of Cilacap with number of 90 peoples. The technique of taking sample in this research used total sampling. The number of sample in this research was 16 respondents. Insomnia scale measuring used Pittsburg Insomnia Rating Scale. Data analysis used frequency distribution and paired t-test. The number of respondents were mostly at the age of 60 to 74 years old (elderly) were 13 respondents (81,25%). Most of them were male with number of 9 respondents (56,25%). The result of statistic experiment was got p value = 0,000 less than ? = 0,05. There was significant difference in a statistic manner between before and after doing gymnastics. So that, there was influence of elderly fit gymnastics towards insomnia scale decreasing at Dewanata Elderly Orphanage of Cilacap.